(untitled) (LínguaTec, 2018)
This narrative intends to describe tools that are being implemented in English Language classrooms, with public high school students in the Federal Institute of Rio Grande do Sul (IFRS), Campus Bento Gonçalves, in Brazil. They allow teachers to better manage their short time with each group of students, as well as provide a wider range of possibilities of exercises to students with different levels of knowledge of the foreign language. The tools presented here may also be of use for more efficient formal and informal assessment, considering that language teachers usually face a large number of students. Some data related to a survey carried out with students, regarding the use of such tools, are also mentioned. These resources save time and provide a more engaging learning environment, making students more autonomous and collaborative.